Tongue Twisters As A Paremiological Unit - Mamataliyeva Navbakhor Xujamberdiyevna (Global Scientific Publishing, 2024)
Tongue twisters, while often perceived as mere linguistic games, can be analyzed as significant paremiological units within a language. As phrases that challenge phonetic articulation, tongue twisters share structural and cultural qualities with proverbs, idioms, and other types of proverbial expressions studied in paremiology. This article explores the linguistic functions, cultural significance, and phonetic patterns of tongue twisters. By examining their role in language acquisition, cognitive development, and cultural transmission, the paper highlights how tongue twisters contribute to the understanding of language structure and its evolution. This analysis underscores their place within the broader framework of paremiology, offering insights into how sound patterns and cultural expressions intertwine
Keywords: Tongue twisters; paremiology; proverbs; idioms